Chemicals evaluation of selected insecticides against Amrasca devastans (Distant) (Hemiptera: Cicadellidae) on brinjal / Muhammad Amin Abd Rahaman - Abd Rahaman, Muhammad Amin (Faculty of Plantation and Agrotechnology, 2015)
Brinjal is one of the most delicious vegetable in the world, however it has been attacked by lots of insect pests. Among of them is Amrasca devastans, the brinjal leafhopper. This insect pest affects the brinjal by nourishing on the leaves and cause "hopper bum" which reduce the productivity of yield. The evaluation of selected insecticides under field conditions showed that their potential to control the population of A. devastans. The application of the chemicals showed the significant reduction in population number of A. devastans. Among the three treatments Confidor, Oshin and control/water, both chemical insecticides showed the significant difference to the control treatment but the Confider and Oshin have no significant difference. The results showed the overall mean population number when compared with the other two treatments Oshin and control, Confider gave the most effective control in population number with a mean of 4.58. While the mean population number of A. devastans for Oshin and water was 5.15 and 12.23 respectively. The chemicals insecticide found to be very efficient and cost-saving to control the A. devastans population number.